1995
DOI: 10.1099/13500872-141-8-1909
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in Klebsiella pneumoniae: a novel gene, ramA, confers a multidrug resistance phenotype in Escherichia coli

Abstract: Spontaneous multidrug-resistant (Mdr) mutants of Klebsiella pneumniae strain ECL8 arose at a frequency of 2.2 x to a range of unrelated antibiotics, including chloramphenicol, tetracycline, nalidixic acid, ampicillin, norfloxacin, trimethoprim and puromycin. A chromosomal fragment from one such mutant was cloned, and found to confer an Mdr phenotype on Escherichia coli K12 cells that was essentially identical to that of the K. pneumoniae mutant. Almost complete loss of the OmpF porin in the E. coli transforman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 52 publications
6
104
0
3
Order By: Relevance
“…The presence of Mdr or similar systems has been reported in Abbreviation: CCCP, carbonyl cyanide rn-chlorophenylhydrazone. (Ariza et al,-l995;Gambino et al, 1993;George et al, 1995;M a et al, 1995;Okusu et al, 1996). Drug efflux can be expressed conjointly to a reduction in drug uptake : examples of a drastic decrease in outer-membrane porins have been reported, pointing to a nodal site in the regulation cascade of the Mdr process (Cohen et al, 1988;Gambino et al, 1993;George et al, 1995).…”
Section: The Emergence Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Mdr or similar systems has been reported in Abbreviation: CCCP, carbonyl cyanide rn-chlorophenylhydrazone. (Ariza et al,-l995;Gambino et al, 1993;George et al, 1995;M a et al, 1995;Okusu et al, 1996). Drug efflux can be expressed conjointly to a reduction in drug uptake : examples of a drastic decrease in outer-membrane porins have been reported, pointing to a nodal site in the regulation cascade of the Mdr process (Cohen et al, 1988;Gambino et al, 1993;George et al, 1995).…”
Section: The Emergence Ofmentioning
confidence: 99%
“…(Ariza et al,-l995;Gambino et al, 1993;George et al, 1995;M a et al, 1995;Okusu et al, 1996). Drug efflux can be expressed conjointly to a reduction in drug uptake : examples of a drastic decrease in outer-membrane porins have been reported, pointing to a nodal site in the regulation cascade of the Mdr process (Cohen et al, 1988;Gambino et al, 1993;George et al, 1995). The spread of several resistance mechanisms and the modulation of the different bacterial responses to antibiotic therapy call for studies of multidrug resistance systems, their identification and their prevalence in strains isolated from hospital units.…”
Section: The Emergence Ofmentioning
confidence: 99%
“…36) It has been also reported that expression of acrA Kp was elevated in a strain of K. pneumoniae in which the expression of ramA was increased. 33) RamA is involved in the expression of acrAB in Enterobacter aerogenes and is closely related to K. pneumoniae.…”
Section: )mentioning
confidence: 99%
“…37) Both RamA and MarA belong to the AraC-XylS transcriptional activator family. 36,38) It is not clear whether RamA is involved in the regulation of acrAB in K. pneumoniae. For these reasons, we also measured the expression level of ramA (Fig.…”
Section: )mentioning
confidence: 99%
“…In Enterobacteriaceae, the development of MDR is under positive regulation by global transcriptional activators that include members of the Ara/XylS superfamily such as MarA, RamA (absent in E. coli) and Rob, as well as the oxidative stress regulon SoxSR [10,[25][26][27][28][29]. Mutations in the corresponding genes are well documented and induce the overproduction of efflux pumps with concomitant repression of porin expression both directly and indirectly [10].…”
Section: Global Regulatorsmentioning
confidence: 99%